Pioglitazone Ameliorates Smooth Muscle Cell Proliferation in Cuff-Induced Neointimal Formation by Both Adiponectin-Dependent and -Independent Pathways - Kubota, Tetsuya (Sci Rep, 2016)
The aim of this study is to elucidate to what degree adiponectin is involved in TZD-mediated amelioration of neointimal formation. We investigated the effect of 3- or 8-weeks’ pioglitazone on cuff-induced neointimal formation in adiponectin-deficient (APN-KO) and wild-type (WT) mice. Pioglitazone for 3 weeks reduced neointimal formation in the WT mice with upregulation of the plasma adiponectin levels, but failed to reduce neointimal formation in the APN-KO mice, suggesting that pioglitazone suppressed neointimal formation by adiponectin-dependent mechanisms. Pioglitazone for 3 weeks suppressed vascular smooth muscle cell (VSMC) proliferation and increased AdipoR2 expression in the WT mice. In vitro, globular adiponectin activated AMPK through both AdipoR1 and AdipoR2, resulting in the inhibition of VSMC proliferation. Interestingly, 8-weeks’ pioglitazone was reduced neointimal formation in APN-KO mice to degree similar to that seen in the WT mice, suggesting that pioglitazone can also suppress neointimal formation via a mechanism independent of adiponectin. Pioglitazone for 8 weeks completely abrogated the increased VSMC proliferation, along with a reduction of cyclin B1 and cyclin D1 expressions and cardiovascular risk profile in the APN-KO mice. In vitro, pioglitazone suppressed these expressions, leading to inhibition of VSMC proliferation. Pioglitazone suppresses neointimal formation via both adiponectin-dependent and adiponectin-independent mechanisms.